Konektivitas Konsumen Generasi Milennial dengan Produk Fast Food pada Era Pemasaran Omnichannel - Windasari, Adita; Lestari, Adyla Mita; Muhandoyo, Muhandoyo (JOPPAS: Journal of Public Policy and Administration Silampari, 2024)
This study aims to determine the omnichannel marketing strategy of fast food restaurants and analyze the connectivity patterns of millennial generation consumers with fast food products. The location of the study was in Malang City with the research object of 3 largest fast food restaurants in Malang City. The sample of this study was millennial generation consumers born in 1980-1999 totaling 300 people. The data analysis method used a descriptive approach with data collection through literature studies and interviews using questionnaires. The study results showed that the omnichannel scenario in the three fast food restaurants was webrooming. The connectivity that occurs between millennial generation consumers and fast food products is dominant through communication channels and sales channels in the form of online media (social media and ordering via online motorcycle taxi applications). Keywords: Millennial, Offline, Omnichannel, Online